Alveolar Soft-Part Sarcoma Presenting with Eosinophilia and Shunt - M Almansori; AR Turner; S Girgis; D Vethanayagam (Canadian Respiratory Journal)
Alveolar soft-part sarcoma (ASPS) is a rare soft tissue tumour found in young adults that usually arises in skeletal muscle and occurs most frequently in the lower limbs. Radiological and pathological findings of ASPS in a 34-year-old man who presented with increasing shortness of breath over a period of four to six weeks with peripheral blood eosinophilia, hypoxemia and a significant arteriovenous shunt are reported. The present article is the fourth report of eosinophilia in association with sarcoma, and the first involving ASPS.